Modeling lacto-vegetarian, pescatarian, and “pescavegan” USDA food patterns and assessing nutrient adequacy for healthy non-pregnant, non-lactating adults - Hess, Julie M.; Comeau, Madeline E. (Frontiers in Nutrition, 2023)
The 2020-2025 Dietary Guidelines for Americans (DGA) includes a Healthy Vegetarian Dietary Pattern (HVDP) with dairy foods and eggs as one of its three recommended dietary patterns for non-pregnant, non-lactating healthy adults. This study evaluates whether pescatarian, lacto-vegetarian, and “pescavegan” adaptations of the HVDP can be nutritionally adequate if modeled with foods recommended by the DGA. The nutrient composition of these three alternative models of the HVDP were assessed at 1800-, 2000-, 2200-, and 2400- kcal/day using similar food pattern modeling procedures as the 2020 DGA. For the pescatarian and pescavegan models, 0.5 ounce-equivalent of refined grains per day was replaced with seafood. For the lacto-vegetarian and pescavegan models, eggs were replaced with equal proportions of the other vegetarian protein foods. In the pescavegan model, dairy foods were replaced by a dairy alternative group comprised of fortified soy milk and soy yogurt. All models at all energy levels were within Acceptable Macronutrient Distribution Ranges (AMDRs) for all macronutrients, contained ≤5% of total kcal from saturated fat, and met recommendations for most micronutrients. Nutrients provided below the Dietary Reference Intakes (DRIs) in these models included iron, sodium, vitamin D, vitamin E, and choline. Micronutreints provided at less than 50% of their respective DRIs included vitamin D and choline. Adapting the HVDP for lacto-vegetarian, pescatarian, and pescavegan dietary patterns provided adequate amounts of macronutrients and most micronutrients.